Antagonistic and plant growth promoting properties of actinomycetes from rhizosphere Deschampsia antarctica È. Desv. (Galindez Island, Antarctica) - Tistechok, S.; Skvortsova, M.; Luzhetskyy, A.; Fedorenko, V.; Parnikoza, I.; Gromyko, O. (Ukrainian Antarctic Journal, 2019)
Aim. The isolation of actinomycetes from Deschampsia antarctica É. Desv. (Galindez Island, Antarctica) rhisosphere and determine their ability to produce compounds with antimicrobial and plant growth promotional properties. Methods. Actinomycetes were isolated using the three different methods: direct inoculation, the roots treatment with an aqueous solution of phenol and heated at 100 °C for 60 minutes. To study the antibacterial activity of actinomycetes, they were plated on the Oatmeal medium and flooded by 0,7% agar with specific test-culture. Antifungal activities were studied by putting the agar block with fungal culture on Petri plates with cultures of actinomycetes. An activity index was determined by the ratio of the diameter zone of the inhibit growth test-cultures to the diameter of the actinomycetes colonies. Plant growth promotion properties were studied by commonly accepted methods. Results. 35 psychotolerant isolates were identified among the 43 actinomycetes isolated from D. antarctica rhizosphere. Almost 42% of actinomycetes isolates were antagonists at least one of typical strain of phytopathogenic bacteria (Pseudomonas savastanoi pv. phaseolicola, Xanthomonas campestris pv. campestris, Agrobacterium tumifaciens, Erwinia amylovora) or fungi (Fusarium oxysporum, Botrytis cinerea, Alternaria alternata). An activity index of most isolates was 3—6, in some isolates — 30—32. The potential plant growth promotion properties of isolates were evaluated. 11 isolates of actinomycetes produced indolyl-3-acetic acid (the level of synthesis was 21,0—62,5 μg/ml), 27 isolates produced siderophores and 6 isolates solubilized phosphorus compounds. Conclusions. Antimicrobial and plant growth promotional properties of the actinomycetes from rhizosphere D. antarctica were evaluated. Phytopathogenic bacteria and fungi antagonists were identified. A number of isolates were characterized by plant growth promotional properties that are combined with the synthesis of antimicrobial compounds. Such properties of isolated actinomycetes may play an important role in the adaptation of Antarctic plants to extreme conditions of existence. The described actinomycetes can be a source of new biologically active compounds and genes that control their biosynthesis.